2008
DOI: 10.1007/s00787-007-0666-4
|View full text |Cite
|
Sign up to set email alerts
|

Can a general health surveillance between birth and 10 months identify children with mental disorder at 1½ year?

Abstract: A general health surveillance program seems to have potentials to identify infants at risk for mental health problems provided standardised measures and specific training of the involved health professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 21 publications
2
21
0
Order By: Relevance
“…Contrary to our hypothesis, we did not find motherechild relationship problems measured during infancy to be predictive of eating behavior problems in preadolescence. The lack of associations may be explained by effective interventions by community health nurses as a part of the general child health surveillance in Denmark [31], but the finding may also reflect that the importance of the motherechild relationship in relation to children's eating differs according to the age and the developmental stage of the child.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our hypothesis, we did not find motherechild relationship problems measured during infancy to be predictive of eating behavior problems in preadolescence. The lack of associations may be explained by effective interventions by community health nurses as a part of the general child health surveillance in Denmark [31], but the finding may also reflect that the importance of the motherechild relationship in relation to children's eating differs according to the age and the developmental stage of the child.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric health care providers suggested that, apart from clinical surveys, parental and physicians' concerns about the children's developmental problems would be supplementary to identify at-risk infants in general health surveillance. 31,32 Moreover, physicians' initial concerns were found as early as 7.5 months of infant age, and they usually noticed the problems earlier than the parents. 32 Therefore, professional concerns in clinical practice, accompanied by further developmental screening, are critical for developmental surveillance for infants.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there is some evidence to suggest that infant mental health problems could be predicted during a routine general health surveillance carried out by non-mental health professionals in early infancy, potentially identifying infants at risk of mental health problems in early life. 39 Perinatal services remain focused on maternal mental health as their main priority: 40 although some monitoring of the mother-baby relationship occurs in an in-patient setting with mothers with the most severe illness, any out-patient work around this is generally performed by health visitors and social work agencies. Parenting capacity and child protection are paramount across psychiatry: Milburn et al 41 highlight the process of assessment of these factors with parents and children of all ages, especially infants in vulnerable families, with consideration towards involvement of statutory measures where necessary.…”
Section: Implications For Mental Health Servicesmentioning
confidence: 99%